Development of basic working loads for metal plate connected timber joints - Yeoh, David (2003)
The purpose of this study is to determine the basic working load (BWL) of metal plate connections in different species of Malaysian timber namely as Kapur (Dryobalanops spp), and Dark Red Meranti (Shorea sp.) .Two types of connections were used, parallel and perpendicular joints, each joints consists of two different orientation of plate to load directions. The study also includes the investigation of strength influence due to gap factors at butt end and at different embedment surface on Dark Red Meranti species. Each type of connection consists of 12 specimens. The samples of the wood connections were experimented under tensile loads for the derivation of their BWL. The size of metal plate is 50 mm (w) x 100 mm (l) x 1 mm (t). All testing and analysis were carried out in accordance to Australian Standard (AS 1649 – 1998). For each test specimens, the maximum load, maximum displacement and failure mode were observed. The values of BWL derived were from the maximum load. It is found that the highest BWL were from the parallel orientation of wood and plate to the load direction with 80 N/tooth and 40.75 N/tooth for Kapur and Dark Red Meranti respectively. From the result of this study, it shows that the orientation plate, wood species, density of the wood and its moisture content influenced the strength of the metal plate connection. However the study on the effect of gap and different embedment level towards BWL were inconclusive due to high variation.